Post-traumatic diabetes insipidus combined with primary polydipsia. Issue 735 (January 1987) - Labib, M.; McPhate, G.; Marks, V.
Abstract : We describe a case of diabetes insipidus after head injury in which thirst persisted despite treatment with DDAVP and normal plasma osmolality. Symptoms were only completely relieved when plasma osmolality was below 270 mosmol/kg. We believe that this might have been due to hypothalamic injury causing resetting of the thirst osmostat. To our knowledge, this type of primary polydipsia has not been described before in association with diabetes insipidus following head injury.